Semantic Relation of Place Toponymy: Reflection of Minangkabau Migration in the West Coast of Sumatra - Triana, Hetti Waluati; Kustati, Martin; Nelmawarni, Nelmawarni; Aziz, Zulfadli; Reflinaldi, Reflinaldi (Humanus, 2022)
This study aims to describe types of meanings and identify the semantic relations of place names, as well as explains the migration in Minangkabau on the West Coast of Sumatra. A qualitative research was used where sources of data were taken from interview, Focus Group Discussion (FGD), and documents. The interview and FGD were conducted to society figures, community leaders and government officials. The documents include the names of 22 sub-districts in 11 districts from four provinces, written sources, and other relics related to the names. The findings show that the place names provide knowledge about the relations of the meaning and socio-cultural values. The relation among the meanings of the place names includes synonymy and antonym that reflects the migration of Minangkabau in West Coast of Sumatra. The results also indicated that toponymy studies are very important because the naming of places has not received attention among the communities and has not been a study of interest.